2015
DOI: 10.1007/s12144-015-9331-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Distinctiveness and Identification with the Furry Fandom

Abstract: We examined perceptions of optimal distinctiveness in the furry fandom and the relationship between this perception and identification with the furry fandom. Selfidentified furries (N=2998) completed measures of optimal distinctiveness that included felt inclusion/belongingness with the fandom and a measure of perceived group distinctiveness from other groups. Participants also completed a measure of identification with the fandom. Results revealed an interaction between felt belongingness and perceived distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The researchers showed that on all factors, including the sense of global influence, ratings of for one’s science fiction fandom were higher than participants’ ratings of their local neighborhood. The findings do not appear that surprising given the importance of belonging for fans as a motivating factor for identification with the group (Reysen, Plante, Roberts, & Gerbasi, 2015; Wann, 1995). Community fulfillment of needs is another concept shown in previous fan research and is evidenced by fans reporting greater subjective well-being resulting from their connection to fan communities (Wann, 2006; Wann, Waddill, Polk, & Weaver, 2011).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…The researchers showed that on all factors, including the sense of global influence, ratings of for one’s science fiction fandom were higher than participants’ ratings of their local neighborhood. The findings do not appear that surprising given the importance of belonging for fans as a motivating factor for identification with the group (Reysen, Plante, Roberts, & Gerbasi, 2015; Wann, 1995). Community fulfillment of needs is another concept shown in previous fan research and is evidenced by fans reporting greater subjective well-being resulting from their connection to fan communities (Wann, 2006; Wann, Waddill, Polk, & Weaver, 2011).…”
mentioning
confidence: 78%
“…A small collection of fans, primed for greater group engagement while being at a convention, seem far more likely to perceive their most accessible in-group as a stronger community than the one they left to attend the convention. Research involving social identity (Tajfel & Turner, 1979) and self-categorization among fans (Reysen et al, 2015) helps to offer further explanation. Groups that fans identify with more, that are made salient at the time of examination by researchers, or by asking participants to think about their top fandom/fan interest, are likely to show higher levels of perceived identification, matching of values, and even a sense of belonging or emotional connection with the group (Jetten, Postmes, & McAuliffe, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The shift from personal to social identity represents an important type of fluidity in the self-concept, and the effect of such a shift is to depersonalize self-conception such that the focus is no longer on “me” and “I”, but on “us” and “we” in contrast to “them” (Onorato and Turner, 2004). Thus, when individuals define themselves as members of a group, they perceive themselves as interchangeable with members of that group and distinct from members of other groups (Reysen et al , 2016). Moreover, it has been suggested that once a group identity is cognitively activated, individuals depersonalize and adopt the norms, values, behaviours and emotions typical of the activated group identity (Reysen et al , 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…They found that each fandom differed somewhat with respect to which of Wann's eight fan motivations were the most strongly tied to fan identity, but all fan groups provided at least some support for the existence of each of the different motivations. Subsequent research has found that several of these motivations consistently emerge as among the strongest associated with fan behavior across fandoms, including belongingness (Reysen, Plante, Roberts, & Gerbasi, 2017), escapism (Chadborn et al, 2017), and self-esteem (Mock, Plante, Reysen, & Gerbasi, 2013).…”
Section: Fan Motivationsmentioning
confidence: 99%